2012
DOI: 10.1186/1471-2105-13-171
|View full text |Cite
|
Sign up to set email alerts
|

An image classification approach to analyze the suppression of plant immunity by the human pathogen SalmonellaTyphimurium

Abstract: BackgroundThe enteric pathogen Salmonella is the causative agent of the majority of food-borne bacterial poisonings. Resent research revealed that colonization of plants by Salmonella is an active infection process. Salmonella changes the metabolism and adjust the plant host by suppressing the defense mechanisms. In this report we developed an automatic algorithm to quantify the symptoms caused by Salmonella infection on Arabidopsis.ResultsThe algorithm is designed to attribute image pixels into one of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Similar to animals or humans, plants respond to colonization of pathogenic bacteria inducing numerous immune responses, among others are oxidative burst and enhanced expression of Pathogenesis Related (PR) genes. Both were observed after inoculation with Salmonella and both were stronger if the inoculation was performed using mutants in T3SS [59,85,86]. Those results suggest that the wild-type strain is able to suppress the immune response.…”
Section: The Function Of T3ss and The Role Of Plant Immune System Durmentioning
confidence: 80%
See 3 more Smart Citations
“…Similar to animals or humans, plants respond to colonization of pathogenic bacteria inducing numerous immune responses, among others are oxidative burst and enhanced expression of Pathogenesis Related (PR) genes. Both were observed after inoculation with Salmonella and both were stronger if the inoculation was performed using mutants in T3SS [59,85,86]. Those results suggest that the wild-type strain is able to suppress the immune response.…”
Section: The Function Of T3ss and The Role Of Plant Immune System Durmentioning
confidence: 80%
“…The inoculation with the wild-type Salmonella strains and mutants in one or both of the T3SSs showed that functional secretion systems are required for eicient plant colonization [59,85,93]. Two observations allow such a conclusion: (1) The mutants had lower proliferation rates when compared to the respective wild type, which suggests that a functional T3SS helps with the colonization of plants; and (2) T3SS mutants induced stronger immune response of the host plant.…”
Section: The Function Of T3ss and The Role Of Plant Immune System Durmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the bleaching effect we observed in the dead plants was also the result of chlorophyll degradation, as measured following ethanol extraction of infected plants (data not shown). Although the use of a qualitative visual endpoint determination in the current method results in a simple and inexpensive assay, the sensitivity of this assay could potentially be improved by automating the quantification of the extent of plant morbidity and chlorophyll degradation by a method similar to that described by Schikora et al [36], who produced a pixellation algorithm to monitor Salmonella Typhimurium infection of Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%